Telaah Kurikulum Pembelajaran Bahasa Arab di SMP Darul Hijrah Putri - Mursyidatul Awaliyah; Ahmad Saidi; Said Taufiqurrahman Bahsin (Tarbawi, 2023)
The Arabic Language curriculum at the Junior High School level plays a central role in developing students' abilities to understand and use the language. Analyzing the curriculum at this level becomes important to evaluate the extent to which the materials, approaches, and teaching methods can meet the needs and abilities of students. The implementation of the Arabic language curriculum can vary depending on the context, learning objectives, and characteristics of the learners, making it important to have a flexible curriculum that can be adapted to the needs of the students according to the developments and challenges perceived by the teachers. SMP Darul Hijrah Putri is part of Pondok Pesantren Darul Hijrah Putri where the educators are alumni of Pondok Modern Gontor, thus the curriculum adopted is also the Gontor curriculum, namely KMI (Kulliyatul Mualimin Al-Islamiyah).